2013
DOI: 10.1186/ar4129
|View full text |Cite
|
Sign up to set email alerts
|

OPN gene polymorphisms influence the risk of knee OA and OPN levels in synovial fluid in a Chinese population

Abstract: IntroductionA body of studies suggests the role of osteopontin (OPN) in onset and development of osteoarthritis (OA), however, the association between OPN polymorphisms and OA susceptibility as well as its clinical features has not been reported.MethodsA total of 750 patients with primary knee OA and 794 healthy volunteer were enrolled as controls. Both OA and control groups were interviewed to obtain demographic and clinical data. Three polymorphisms of OPN gene, namely, -156GG/G, -443C/T and -66T/G were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
(36 reference statements)
1
21
0
1
Order By: Relevance
“…The polymorphic site -443 is associated with osteoarthritis risk and severity. Thrombin-cleaved osteopontin levels in the synovial fluid are lower in subjects with the -443T/T genotype, resulting in milder disease (25). In the present study the T allele was represented more frequently than the C allele at high tumor grade and in tumors with high osteopontin RNA levels (of note, for a subset of samples this result was confirmed by reanalysis in an external core facility to exclude the possibility of an erroneous data set).…”
Section: Discussionsupporting
confidence: 69%
“…The polymorphic site -443 is associated with osteoarthritis risk and severity. Thrombin-cleaved osteopontin levels in the synovial fluid are lower in subjects with the -443T/T genotype, resulting in milder disease (25). In the present study the T allele was represented more frequently than the C allele at high tumor grade and in tumors with high osteopontin RNA levels (of note, for a subset of samples this result was confirmed by reanalysis in an external core facility to exclude the possibility of an erroneous data set).…”
Section: Discussionsupporting
confidence: 69%
“…Reaction condition consisted of pre incubation at 50 °C for 2 min, at 95 °C for 10 min, and followed by 40 cycles of 95 °C for 15 s and 60 °C for 1 min. Amplifications were performed in an ABI Prism® 7500 Sequence Detection System (Applied Biosystems) [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, rs17524488 and rs11730582 may have different effects on disease risk, although both of them have been shown to be able to modify SPP1 expression in vitro. Recently, another study by Jiang et al reported significant associations of rs11730582 and rs28357094, but not rs17524488, in SPP1 gene with knee OA risk (Jiang et al, 2013). It is hard to explain exactly the reason for such differences, but some hints can be found in these two studies.…”
Section: Discussionmentioning
confidence: 96%